Development of a novel parallel double-stage yielding buckling restrained brace: Theoretical, experimental, and numerical investigations. (1st June 2023) - Yang, Cantian; Xie, Linlin; An, Nan; Li, Aiqun; Liu, Qianmin; Wang, Xinyu
Abstract: In this study, a novel parallel double-stage yielding buckling restrained brace (PDYBRB) is developed. It comprises parallel core system, load-transfer system, and restrainer system. The first- and second-stage cores are set in parallel and activate asynchronously. The double-stage yielding characteristics and full utilization of the two cores are expected for such a PDYBRB, thus leading to a double-stage working mechanism and good energy dissipation capacity. According to the working mechanism of the PDYBRB, theoretical analyses are first conducted, and the equations for design are proposed. Subsequently, three full-scale PDYBRB specimens are designed using the theoretical equations and tested under cyclic loading, and the feasibility and reliability of the PDYBRB and proposed equations are validated. The effectiveness of varying the design parameters for adjusting the double-stage yielding behavior are verified. Furthermore, a numerical investigation based on the refined finite element model is conducted, the working mechanism and hysteretic behavior of the PDYBRB are well simulated. The research outcomes can provide a valuable reference for the development of novel buckling restrained braces. Highlights: A novel parallel double-stage yielding buckling restrained brace (PDYBRB) is developed. Theoretical equations are proposed to predict the skeleton curve of PDYBRB. Three full-scale PDYBRBs are tested to validate the working mechanism of PDYBRB. A refined numerical simulation method is recommended and validated. The reliability of PDYBRB and its theoretical equations is verified.